2016
DOI: 10.4103/0975-1475.195114
|View full text |Cite
|
Sign up to set email alerts
|

Gender determination by radiographic analysis of mental foramen in the Maharashtra population of India

Abstract: Context:Identification of gender is of primary importance in forensic investigations when only fragment of skull remains. Mandible is a hard bone and exhibits a high degree of sexual dimorphism. Gender differences were observed in the height of mandible, gonial angle, bigonial breadth, bicondylar breadth, and position of mental foramen (MF).Aims of the Study:The purpose of this study is to evaluate gender differences in distances from superior border of MF (SMF) and inferior border of MF (IMF) to the lower bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Figure 3(c) is the orthopantomogram X-ray image. This type of imaging displays a complete panoramic view of teeth [ 12 – 14 ]. Dataset of orthopantomogram (OPG) was used in this paper for detection of gender and age estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3(c) is the orthopantomogram X-ray image. This type of imaging displays a complete panoramic view of teeth [ 12 – 14 ]. Dataset of orthopantomogram (OPG) was used in this paper for detection of gender and age estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few other studies have also explored how well the osteologic criteria may distinguish races among persons who live in a specific geographic area. [ 19 - 21 ] The potential of these osteologic markers to determine gender has only been briefly explored in the literature. Samatha et al .…”
Section: Discussionmentioning
confidence: 99%
“…While, the distance between the MF and the alveolar crest due to resorption of the later 19,20 . It was also reported that the length from the lower border of the lower jaw to the MF shows gender dimorphism, and orthopantomography or panoramic radiography (OPG) is a sufficient way for the assembly of planned measurements and determination of sex from skeletal remnant [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%